Legal aid in Malaysia - Sardar Baig, Farheen Baig (CLJ Publication, 2014)
Access to justice is a universal human right,as reflected in the Universal Declaration of Human Rights and many international and regional human rights instruments, as well as the United Nations 1990 Basic Principles on the Role of Lawyers. Based on this firm conviction, we believe that access to lawyers and legal services should be guaranteed and made available to all, especially to the poor and other disadvantaged persons, when necessary to achieve a just and fair result.